2012
DOI: 10.3382/ps.2012-02306
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic innate immunity in broiler chickens supplemented with yeast-derived carbohydrates

Abstract: A study was conducted to assess the effect of yeast-derived carbohydrates (YDC) on performance and innate immune responses of broiler chickens. In total, 1,080 one-day-old birds were randomly assigned to one of 3 dietary treatments (n = 360): a standard broiler diet containing monensin (control), control + bacitracin methylene disalycylate (BMD), and YDC treatment (control + YDC at 0.02%, 0.01%, and 0.005% for starter, grower, and finisher, respectively). Weekly BW, feed intake (FI), and feed conversion ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 45 publications
11
44
2
5
Order By: Relevance
“…Intestinal morphometry revealed no differences between dietary treatments in terms of fold length, in agreement with previous studies in other vertebrate species [34,39,58]. However, fold width was reduced in fish fed cMOS, which could be due to a reduced engrossment of the submucosa within the fold basis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Intestinal morphometry revealed no differences between dietary treatments in terms of fold length, in agreement with previous studies in other vertebrate species [34,39,58]. However, fold width was reduced in fish fed cMOS, which could be due to a reduced engrossment of the submucosa within the fold basis.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, dietary cMOS inclusion reduces the homogeneity and diversity of the ileum and caecal microflora in rabbits [36], without effect on nutrient digestibility or carcass quality of meat [37]. Besides, cMOS supplementation modulated gene expression of some immune-related genes involved in cellular immune response, mucus production, antimicrobial and inflammatory responses obtaining, in some cases, a great similarity to those profiles obtained after an antibiotic pulse supplementation for other intensive produced animals [29e31, 33,38,39].…”
Section: Introductionmentioning
confidence: 91%
“…Despite the positive effects of the use of MoS on the immune system reported by several authors (ShAShIDhARA & DEVEGowDA, 2003;MuNyAKA et al, 2012) in the present study was not observed significant difference (P>0.05) between treatments on the levels of IgG to infectious bronchitis. Probably the use of wood shaving beds of two consecutive batches was not sufficient for stimulation of increase in the IgG production by immune system.…”
Section: Resultscontrasting
confidence: 53%
“…Regarding on the action of Mannan oligosaccharides MuNyAKA et al (2012) stated that the differences between results reported in the studies may be due to differences between experimental protocols, production phase, conditions in which the experiment was conducted, source, type, and concentration of MoS used in the additive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation